Comprehensive geriatric assessment in patients with gastric and gastroesophageal adenocarcinoma undergoing gastrectomy. Issue 8 (19th October 2015) - Pujara, Deep; Mansfield, Paul; Ajani, Jaffer; Blum, Mariela; Elimova, Elena; Chiang, Yi‐Ju; Das, Prajnan; Badgwell, Brian
Abstract : Objective: The purpose of this study was to identify clinical and geriatric assessment variables associated with outcome in patients with gastric adenocarcinoma who have undergone gastrectomy. Methods: We reviewed demographic, clinical, and geriatric assessment variables, including recent falls, pain, performance status, American Society of Anesthesiologists score, assistive device use, comorbidity, polypharmacy, and weight change, for patients undergoing gastrectomy between 2005 and 2014. Outcome variables included morbidity, mortality, hospital length of stay, and readmission. Results: Of 279 patients, 133 (48%) underwent total gastrectomy. The 90‐day major morbidity rate was 24% and the mortality rate was 1%. Length of hospital stay ≥14 days occurred in 38%, with readmission within 30 days in 13%. On multivariate analysis, gastroesophageal junction involvement, (odds ratio [OR] 2.5, 95% confidence interval [1.1–5.8]), additional organ resection, (OR 3.2, [1.6–6.3]), pain score >0 (OR 3.8, [1.6–8.7]), Eastern Cooperative Oncology Group performance status >0, (OR 2.3, [1.2–4.6]), and polypharmacy (OR 2.4, [1.1–5.2]) were associated with major morbidity. Hospital stay ≥14 days was associated with age ≥75 years (OR 3.9, [1.7–9.2]), total gastrectomy (OR 3.5, [2.0–6.3]), performance status >0 (OR 1.8, [1.0–3.2]), and preoperative chemotherapy (OR 0.3, [0.2–0.7]). Conclusions: Future studies are needed to identify methods to improve performance status, as this may improve postoperative complications and resource utilization. J. Surg. Oncol. 2015;112:883–887 . © 2015 Wiley Periodicals, Inc.